Pemanfaatan dan langkah langkah pembuatan surat lamaran kerja dan CV pada MS Word - Syahlaa Maulana; Rahma Fahmadina Lubis; Nurleli Nurleli; Nurbaiti Nurbaiti (Universitas Muhammadiyah Enrekang, 2022)
This study attempts to investigate technical advancements in the nation, which cannot be compared to developed nations but has a great deal of potential for natural and human resources. A minimum level of basic knowledge of sophisticated information processing tools has been required for decades, and has even expanded in this century, especially